Effects of veneer drying at high temperature and chemical treatments on equilibrium moisture content of plywood - Aydin, Ismail (Maderas. Ciencia y Tecnología, 2025)
Moisture content (MC) is one of the most important factors that can affect many physical and mechanical properties of wood and veneers. MC strongly affects the final strength and durability of joints, development of surface checks in the wood and dimensional stability of the bonded assembly. In this study, plywood panels made from Alnus glutinosa (Alder), Fagus orientalis (Beech) and Picea orientalis (Spruce) wood veneers were treated with ammonium acetate, borax and boric acid by using dipping method to test for their equilibrium moisture content (EMC). Borax and boric acid solutions were used for fire-retardancy, and ammonium acetate for reducing formaldehyde emission. Two different veneer drying temperatures (20°C and 180°C) were used to reveal the effects of veneer drying at high temperature on the hygroscopicity of plywood panels. EMC values of alder, beech and spruce panels decreased significantly with veneer drying at high temperature. Picea orientalis (Spruce) plywood panels had the highest EMC values and followed by Alnus glutinosa (Alder) and Fagus orientalis (Beech) panels. EMC values of plywood panels increased significantly for both drying temperatures after ammonium acetate, borax and boric acid treatments.